2004
DOI: 10.1158/0008-5472.can-03-3763
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Blockade of Platelet-Derived Growth Factor-Receptor and Epidermal Growth Factor-Receptor Signaling and Systemic Administration of Paclitaxel as Therapy for Human Prostate Cancer Metastasis in Bone of Nude Mice

Abstract: Once prostate cancer metastasizes to bone, conventional chemotherapy is largely ineffective. We hypothesized that inhibition of phosphorylation of the epidermal growth factor receptor (EGF-R) and platelet-derived growth factor receptor (PDGF-R) expressed on tumor cells and tumorassociated endothelial cells, which is associated with tumor progression, in combination with paclitaxel would inhibit experimental prostate cancer bone metastasis and preserve bone structure. We tested this hypothesis in nude mice, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 62 publications
2
83
1
2
Order By: Relevance
“…To study the biology of bone metastases secondary to FTC, we adopted the established murine model of bone lesions (15,36,39) by injecting the WRO cells into the tibia of athymic nude mice followed with weekly radiographic imaging. By the start of the third week, early signs of bone lesions, as evidenced by thinning of the bone, were evident (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To study the biology of bone metastases secondary to FTC, we adopted the established murine model of bone lesions (15,36,39) by injecting the WRO cells into the tibia of athymic nude mice followed with weekly radiographic imaging. By the start of the third week, early signs of bone lesions, as evidenced by thinning of the bone, were evident (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the effect of AEE788 on the in vivo growth of FTC cells in bone, the previously described mouse model was used (15,36,39). Digital radiography of the injected tibias revealed that 80% of the mice in the control group had progressive bone lysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of our findings, Imatinib is successful in the treatment of aggressive systemic mastocytosis 24 and is now considered a standard first-line therapy for GIST tumors 25 as well as to enhance the effects of chemotherapy in a mouse model of PC metastasis. 34 Unfortunately, the use of Imatinib to specifically evaluate the importance of mast cells in a preclinical setting is limited. Based on our findings, however, it seems plausible that the reduction of mast cells after Imatinib treatment could be of therapeutic value.…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib (Gleevec, Novartis Pharmaceuticals Corp., East Hanover, NJ, USA) is a synthetic small molecule that inhibits phosphorylation of a number of tyrosine kinase receptors including PDGFR, c-kit, and bcr-abl (Buchdunger et al, 1995;George, 2003;Matei et al, 2004). It decreases proliferation of both tumour and stromal cells (George, 2003;Furuhashi et al, 2004;Kim et al, 2004;Matei et al, 2004;Ostman, 2004). In colonic xenografts, Pietras et al (2001) demonstrated that imatinib decreases IFP and thereby increases transcapillary transport of small molecules.…”
mentioning
confidence: 99%